2012
DOI: 10.1007/s00296-011-2322-z
|View full text |Cite
|
Sign up to set email alerts
|

Hypokalemic periodic paralysis in Sjogren’s syndrome secondary to distal renal tubular acidosis

Abstract: We report a 53-year-old Turkish female presented with progressive weakness and mild dyspnea. Laboratory results demonstrated severe hypokalemia with hyperchloremic metabolic acidosis. The urinary anion gap was positive in the presence of acidemia, thus she was diagnosed with hypokalemic paralysis from a severe distal renal tubular acidosis (RTA). Immunologic work-up showed a strongly positive ANA of 1:3,200 and positive antibodies to SSA and SSB. Schirmer's test was abnormal. Autoimmune and other tests reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 16 publications
1
23
0
1
Order By: Relevance
“…In any event, the potassium wasting can be severe and lead to hypokalemic paralysis (36,37). In this patient, the addition of topiramate effectively led to the development of proximal RTA as well as possibly worsening of the distal RTA (due to complementary defects in distal acidification from the drug and from Sjögren syndrome).…”
Section: Question 2bmentioning
confidence: 92%
See 1 more Smart Citation
“…In any event, the potassium wasting can be severe and lead to hypokalemic paralysis (36,37). In this patient, the addition of topiramate effectively led to the development of proximal RTA as well as possibly worsening of the distal RTA (due to complementary defects in distal acidification from the drug and from Sjögren syndrome).…”
Section: Question 2bmentioning
confidence: 92%
“…Most of these patients had ocular and dental symptoms consistent with the diagnosis of Sjögren syndrome. Of note, hypokalemia in these patients can be severe and may lead to hypokalemic paralysis (34,36,37).…”
Section: Question 2amentioning
confidence: 99%
“…Severe hypokalemia and paralysis due to dRTA is an unusual initial presentation of Sjögren's syndrome [6,7]. Palkar et al [8] also reported a case of Sjögren's syndrome that presented with acute quadriparesis, bulbar weakness, atrial fibrillation, and ventricular ectopics due to hypokalemic dRTA.…”
Section: Discussionmentioning
confidence: 99%
“…6 Occasionally, this hypokalemia is sufficiently severe to produce paralysis or respiratory arrest. 9 In adults, autoimmune diseases are major causes of dRTA, 3 and this may be its presenting manifestation. Thus, adults with apparently idiopathic dRTA should be evaluated for these conditions.…”
Section: Discussionmentioning
confidence: 99%